TÜRKİYE TÜRKÇESİNDEKİ DEYİMLER ÜZERİNE BİR DİL İNCELEMESİ (2 CİLT) - SİNAN, AHMET TURAN (Fırat Üniveristesi, 2000)
The aim of -this study named A Language investigation On I Q. ı' O «^3 Turkisn is to investigate the structures and functions of idioms in Turkish. Idioms were investigated from the point of sound, morphem and meaning. In most of the idioms finding syllabic meter pauses used widely in Turkish (folk) poems shows that idioms have formed together with harmonic elements. Idioms are the products of anonym language. Some of the idioms have a relation with jokes. Proverbs and idioms are sometimes misused. They are mostly the idioms which are stereotyped with morphem and time affixes. Those idioms, which are in the forms of sentence are used in present time and imperative sentences. Although idioms in Turkish are stereotyped sentences, it is seen that some words at the beginning, middle and end of the sentence changes their place with some synonym words. 10790 idioms, which are 63 % of them, consist of two words, 3918 idioms, 22.8 %, consist of three words and 1592 of them, 9 %, consist of four words. It is possible to divide Turkish idioms into two parts; those ending with infinitive and those not. Two thirds of the idioms ends with infinitive. The other one-third of them consist of different forms such as definite noun phrase, indefinite noun phrase, adjective phrase, gerunds, participes, adverbials. There have been 11901 idioms, 69.4 %, in the form of compound word group. Of 8493 consist of two words while nouns in 3892 idioms possess no inflection suffixes. The idioms stereotyped as sentence can be regular or inverted. Simple and co pound idioms sentences are used as affirmative, negative and internegative forms. Full list of the idioms in Turkish was given in Index. J
A language investigation on idioms in Turkish
Keywords: Dilbilim; Linguistics; Türk Dili ve Edebiyatı; Turkish Language and Literature